2020
DOI: 10.1016/j.trd.2020.102572
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting environmental practice adoption at small European airports: An investigation

Abstract: Highlights Examines the adoption of environmental practices (EPs) by small European airports handling under 5 m passengers a year. TOE framework is used as the basis for an online survey of over 400 airports. Airports are classified into 3 groups according to their level of EP engagement. Relative size of small airports as well as other variables affects the extent of EP adoption. Scope for greater EP adoption exists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…The airport business literature also pointed out the possibility of these types of divergences between specific category airports. For instance, commercial investment opportunities ( Fasone, Kofler and Scuderi, 2016 ), the levels of competition on efficiency ( Merkert and Mangia, 2014 ) or ecologic impact ( Harley, Timmis and Budd, 2020 ) had shown variations for small and remote airports. During the pandemic, it could be observed that the small and medium-sized airports with strong domestic markets were seen as having more advantages in the short term compared to hub airports that depended on connectivity, especially if they had government ownership.…”
Section: Discussionmentioning
confidence: 99%
“…The airport business literature also pointed out the possibility of these types of divergences between specific category airports. For instance, commercial investment opportunities ( Fasone, Kofler and Scuderi, 2016 ), the levels of competition on efficiency ( Merkert and Mangia, 2014 ) or ecologic impact ( Harley, Timmis and Budd, 2020 ) had shown variations for small and remote airports. During the pandemic, it could be observed that the small and medium-sized airports with strong domestic markets were seen as having more advantages in the short term compared to hub airports that depended on connectivity, especially if they had government ownership.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the majority at the global level recognize the impact of their daily usage behavior on the ecology and focus on reducing risks. These people with ecological concerns seek to protect the environment and display positive word of mouth regarding EFTs (Harley et al, 2020). Researchers are therefore paying closer attention, based on their PEI, to the desire of households to purchase EFTs (Debnath et al, 2021).…”
Section: Perceived Environmental Importancementioning
confidence: 99%
“…It has been believed that households are sensitive to emotions associated with environmental concerns, which may provide the spark to adopt EFTs (Zhang et al, 2015). Also, the works done in the United States, China, and Germany uncovered that households with enhanced preferences towards environmental concerns are more likely to adopt EFTs (Harley et al, 2020). It has been argued that the households also feel an emotional advantage as they contribute positively by making the environment less degraded (Michelsen and Madlener, 2013).…”
Section: Pei and Eft Adoption Intentionmentioning
confidence: 99%
“…The aim of the study by Harley et al (2020) is to explore the range of environmental practices used at small European airports and identify the factors affecting their adoption. Findings from online surveys of 413 small airports reveal that the most widely adopted environmental practices relate to noise reduction and waste management.…”
Section: Literature Reviewmentioning
confidence: 99%